Projeto de controle robusto chaveado com falhas nos sensores - Buzetti, Ariel Starcke [UNESP] (2017)
This work addresses a recurring subject in practical implementations of automatic control systems, which is the sensor measurement failure. Thus, the state vector available for feedback, denominated x_ M(t), presents polytopic uncertainties. One of the contributions of this work is an adequate state space representation of a linear time-invariant system using x_ M(t), considering that the measurement uncertainties are time-invariant. Then, using this representation, is proposed a design procedure of a switched control that ensures the stability with a given minimum decay rate (beta) of the controlled system. It is also shown a theorem that decreases the controller's norm to avoid saturation problems and it is demonstrated how to choose the polytope's vertices to decrease the system's conservativeness. A theoretical analysis and simulation results show that the proposed switched control procedure offers less conservative conditions than that provided by using the classical controller with only one gain. This work also presents a controller design that ensures the stability, with a given minimum decay rate, of the controlled system, even if the sensor failure varies in time. Both control designs are based on linear matrix inequalities (LMIs) and use a quadratic Lyapunov function. A practical implementation for controlling a 2D ball balancer system confirms the efficiency of both proposed methods.